A study of noise pollution level in and around educational institutions infrastructure provision and renovation - Ibrahim, Ainaa Nawwarah; Bachok, Syahriah; Mohamed Osman, Mariana (2011)
This paper deals with noise pollution levels in and around educational institution. Transport noise is an increasingly prominent feature of the urban environment. The serious and growing noise problem is the result of rapid development and population growth. The data for this research was collected by using noise decimator placed at three fixed locations and results were collected at three different time durations for every 5 minute intervals. Result shows that noise level differed depending on time of the day and location of the area. Thus, this paper recommends natural and artificial buffer zones to be implemented in order to minimize the impact of noise pollution around educational institutions. Keywords: Noise pollution, educational institutions